2015
DOI: 10.1101/030742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What’s in my pot? Real-time species identification on the MinION™

Abstract: Whole genome sequencing on next-generation instruments provides an unbiased way to identify the organisms present in complex metagenomic samples. However, the time-to-result can be protracted because of fixed-time sequencing runs and cumbersome bioinformatics workflows. This limits the utility of the approach in settings where rapid species identification is crucial, such as in the quality control of food-chain components, or in during an outbreak of an infectious disease. Here we present What′s in my Pot? (WI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 22 publications
0
103
0
Order By: Relevance
“…This opens up an array of opportunities in the field of metagenomics and pathogen identification, particularly with the feasibility of portable sequencing [17,18]. PCR-free library preparation techniques offer quantitative and qualitative cancer profiling, immunome profiling and mtDNA profiling.…”
Section: Resultsmentioning
confidence: 99%
“…This opens up an array of opportunities in the field of metagenomics and pathogen identification, particularly with the feasibility of portable sequencing [17,18]. PCR-free library preparation techniques offer quantitative and qualitative cancer profiling, immunome profiling and mtDNA profiling.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, the study, which produced the in vitro reads (Cuscó et al 2018), used the WIMP workflow which was published specifically for the MinION (Juul et al 2015). Thus, MetaG is powerful enough to beat algorithms at their own game.…”
Section: Discussionmentioning
confidence: 99%
“…After the promising results from the previous analyses, we reanalyzed genuine Nanopore sequences from a bacterial community with a known abundance distribution. The data generated by Cuscó and coworkers had been previously analyzed by the authors using the Nanopore specific What's in my Pot (WIMP) workflow (Cuscó et al 2018;Juul et al 2015).…”
Section: Analysis Of a Minion Mock Samplementioning
confidence: 99%
“…In addition, we ran a blank sample to control for possible contamination during extractions and PCRs. Bioinformatic analyses were carried out using ONT's WIMP software (Juul et al, 2015). For PCR conditions and a full protocol see Protocols.io .…”
Section: Case Studiesmentioning
confidence: 99%
“…The fewest reads (state reads) were unfortunately obtained from the flowcell running the 16s and 18s metagenomics libraries. However, subsequent pilot analyses on WIMP (Juul et al, 2015) indicated some success, but coverage overlap is yet to be assessed.…”
Section: Portable Sequencing In the Amazon Rainforestmentioning
confidence: 99%